2016
DOI: 10.1016/j.ijid.2016.02.735
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia in paediatric: Epidemiology and aetiology at tertiary care centre, Malaysia

Abstract: Conclusion:In this cohort of infants, ARI incidence was 1.8 episodes per year per infant; 95% were URTIs. Viruses were identified in 63.3% episodes and the common viruses detected were RV, RSV and parainfluenza virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…When screening the citations of the 80 studies, we identified an additional four studies that met our inclusion criteria, yielding a total of 84 eligible studies for analysis ( figure 1 ). 6 , 15 , 16 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ,…”
Section: Resultsmentioning
confidence: 99%
“…When screening the citations of the 80 studies, we identified an additional four studies that met our inclusion criteria, yielding a total of 84 eligible studies for analysis ( figure 1 ). 6 , 15 , 16 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ,…”
Section: Resultsmentioning
confidence: 99%
“…Además, se evidenció SARM en 52 % de los casos, lo que resulta preocupante dado el origen comunitario, siendo superior a los reportes por los grupos GREBO y GERMEN (30 y 22 %) en Colombia y, en general, en América y Europa (2,9-23 %), en cuyos países se ha evidenciado, además, una disminución de la frecuencia de estas cepas en varios estudios de seguimiento; no obstante, llama la atención que en ellos no se registró la diferencia estadística esperada entre las cepas resistentes y las sensibles en cuanto a la mortalidad y el ingreso a las unidades de cuidados intensivos pediátricos, tal como se ha hecho en algunos reportes, lo que sugiere una acentuada agresividad de Staphylococcus sensible a la meticilina adquirido en la comunidad (6,8,13). Los focos de infección más frecuentes fueron los tejidos blandos y osteoarticulares, lo que coincide con lo reportado más frecuentemente en la literatura médica especializada (14,15).…”
Section: Discussionunclassified
“…1 Information about etiological agents involved in causing community-acquired bacteremia and their antibiotic resistance pattern will help to improve empiric antibiotic therapy and consequently patient outcomes. 2 In developing countries, Staphylococcus aureus, Klebsiella spp. and Escherichia coli account for 55% (95% con dence interval (CI) 39-70%) of culture positive sepsis among neonates, while in infants the most prevalent pathogens are S. aureus, E. coli, Klebsiella spp., S. pneumoniae and Salmonella spp., which account for 59% (95% CI 26-92%) of culture-positive sepsis.…”
Section: Introductionmentioning
confidence: 99%